Linguistic Strategies Analysis On The Official Website Of Indonesia Tourism (Www.Indonesia.Travel) - Khaira Reizavira (Universitas Muhammadiyah Sumatera Utara, 2021)
This research deals with Linguistic Strategy in the text on the Official Website of Indonesia Tourism (www.indonesia.travel). It is aimed to investigated the type of linguistic strategy based on functions and language features and the realization of lainguistic strategy on the Official Website of Indonesia Tourism. The researcher is applied descriptive qualitative. The data of this research is the text contained on the Official Website of Indonesia Tourism. There are 100 data that were analyzed based on Miles and Huberman, including condensation data, display data and conclusion drawing. The research finding showed that there were two types of linguistic strategy used in the official website of Indonesian tourism, namely: Informative Strategy and Persuasive Strategy. It also found that linguistic strategy was realized in Indonesian tourism websites through five Interactional Metadiscourse markers based on the theory of Hyland and Tse (2004) namely Hedges, Booster, Attitude Markers, Engagement Markers and Self-mentions. Keywords : Linguistic Startegy, Official Website of Indonesia Tourism